Industrial training report: Social Security Organization (SOCSO) / Mohd Fazil Ali - Ali, Mohd Fazil (Perpustakaan Tengku Anis, 2017)
The trainee undergoing industrial training based on the period from 1st February 2017 to 15th June 2017 in Social Security Organization (SOCSO) Ator Seta, as part of requirement in completing course for the Bachelor of Info. Science (Hons.) Information System Management. SOCSO is an abbreviation for Social Security Organization which is a government body that provides social security protection to all employees. All of industrial training students will be given a rotation between 4 departments (Administration, Enforcement, Recovery, and Benefit) in SOCSO A/or Setar. During the 20 weeks period of training, students will be supervised and monitored by a supervisor. The trainee was assigned a special project tor Enforcement Department by organization supervisor, Mr. Ahmad Firdaus Bin Hashim (Head Unit of Enforcement Department). The trainee required to develop a records management system which computerized several records in Enforcement Department. The trainee also required to learn about the basic operation and procedures of the organization in every department.